Synthesis, Characterization, and In Vitro Studies of an Reactive Oxygen Species (ROS)-Responsive Methoxy Polyethylene Glycol-Thioketal-Melphalan Prodrug for Glioblastoma Treatment - Oddone, Natalia; Boury, Frank; Garcion, Emmanuel; Grabrucker, Andreas M.; Martinez, M. Carmen; Da Ros, Federica; Janaszewska, Anna; Forni, Flavio; Vandelli, Maria Angela; Tosi, Giovanni; Ruozi, Barbara; Duskey, Jason T. (Frontiers in Pharmacology, 2020)
Glioblastoma (GBM) is the most frequent and aggressive primary tumor of the brain, and accounts for a life expectancy in patients diagnosed with this disease of only 15 months. Hence, more effective therapies against this malignancy are urgently needed. Several diseases, including cancer, are featured by high levels of ROS, which are possible GBM hallmarks to target or benefit from. Therefore, covalent linkage of drugs to ROS-responsive molecules can be exploited aiming for a selective drug release within relevant pathological environments. In this work, we designed a new ROS-responsive prodrug with Melphalan (MPH), covalently coupled with methoxy polyethylene glycol (mPEG) through a ROS-cleavable group Thioketal (TK), demonstrating to be able to self-assembly in nanosized micelles. Full chemical-physical characterization was conducted on polymeric-prodrug and proper controls. In vitro cytotoxicity of this ROS-responsive prodrug was assayed on different GBM cell lines and “healthy” astrocyte cells and compared with its non-ROS responsive counterpart, underlying antitumoral activity of ROS-responsive prodrug on GBM cells expressing high levels of ROS, higher than the non-ROS-responsive prodrug. Furthermore, safety tests confirmed absence of any cytotoxic effects on healthy cells (i.e. astrocytes). On the other hand, the combination treatment with this ROS-responsive prodrug and X-ray irradiation on human GBM cells resulted in an increase in antitumoral effect, probably connected to radiotherapy. Hence, these results represent a starting point for a rationale design of innovative and tailored ROS-responsive prodrugs to be used in GBM therapy and in combination with radiotherapy.